Effects of physical training programs on female tennis players` performance: a systematic review and meta-analysis - Deng, N.; Soh, K. G.; Abdullah, B.; Huang, D.; Sun, H.; Xiao, W (Frontiers in Physiology, 2023)
Background: Tennis is among the world`s most popular and well-studied sports. Physical training has commonly been used as an intervention among athletes. However, a comprehensive review of the literature on the effects of physical training programs on female tennis players` performance is lacking. Therefore, this systematic review and meta-analysis aimed to determine the effects of physical training on performance outcomes in female tennis players.